The duration use and causes of discontinuation IUD in Sarvabad - hesami, kazhal; savadzade, shahin; khosravi, farangis (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim The intrauterine device (IUD) is the most widely used reversible method of contraception. Discontinuation of various contraceptive methods can cause unplanned and unwanted pregnancies. The aim of this study was to determine duration use and causes of discontinuation IUD in Sarvabad in 2005-2008.